If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x * 5x + -7x + 2 = 0 Reorder the terms for easier multiplication: 5 * 5x * x + -7x + 2 = 0 Multiply 5 * 5 25x * x + -7x + 2 = 0 Multiply x * x 25x2 + -7x + 2 = 0 Reorder the terms: 2 + -7x + 25x2 = 0 Solving 2 + -7x + 25x2 = 0 Solving for variable 'x'. Begin completing the square. Divide all terms by 25 the coefficient of the squared term: Divide each side by '25'. 0.08 + -0.28x + x2 = 0 Move the constant term to the right: Add '-0.08' to each side of the equation. 0.08 + -0.28x + -0.08 + x2 = 0 + -0.08 Reorder the terms: 0.08 + -0.08 + -0.28x + x2 = 0 + -0.08 Combine like terms: 0.08 + -0.08 = 0.00 0.00 + -0.28x + x2 = 0 + -0.08 -0.28x + x2 = 0 + -0.08 Combine like terms: 0 + -0.08 = -0.08 -0.28x + x2 = -0.08 The x term is -0.28x. Take half its coefficient (-0.14). Square it (0.0196) and add it to both sides. Add '0.0196' to each side of the equation. -0.28x + 0.0196 + x2 = -0.08 + 0.0196 Reorder the terms: 0.0196 + -0.28x + x2 = -0.08 + 0.0196 Combine like terms: -0.08 + 0.0196 = -0.0604 0.0196 + -0.28x + x2 = -0.0604 Factor a perfect square on the left side: (x + -0.14)(x + -0.14) = -0.0604 Can't calculate square root of the right side. The solution to this equation could not be determined.
| 8y+6y-2y=36 | | 0.5=0.2-10 | | X*x*x+4x*4x-12x=0 | | Log(2)16=4 | | -54=-42t | | 325+.25y=x | | 8c-3c+2=-8 | | (x+6)/2=-7 | | 2x*2x-10x+12=0 | | 8b-6= | | 5t-1=35-t | | 585=(X*4^1.25)/22^0.5 | | 4(5x-3)+6=-4 | | 585=(X*4^1.25)/4^0.5 | | 585=X*4^2/4^3 | | 5x-7=3x+33 | | 35x+20=125 | | 60=1.30x | | 0=15.75+3.2b | | -x/5=8 | | -20n-12=48 | | 12-2n=6 | | 20x+9=-8x+11 | | -8n+12n=-100 | | 20x+9=-9x+18 | | 20x+-6=-5x+-2 | | 0.3x=0.21 | | 20x+5=-9x+28 | | x/(2/7)=49 | | 20x+-5=5x+40 | | x*7-12=23 | | -25n+7= |